Fault Characteristics and Protection of Distributed Solar Generation - Badal Bisen (AG Volumes, 2021)
Low current defect, insignificant negative, and zero series currents are the characteristics of inverterbased distributed energy sources (DERs). Knowledge of the fault characteristics of DER is required for the investigation and protection of relays. For the most part, no studies have been done to examine how faults affect the DER model. This article focuses on Dominion Energy’s flaws. Of illustrate that the real reaction to DER mistakes may be different than previously thought, stopper defects are studied. It was necessary to model any possible MATLAB-related impact on this study using an advanced simulation environment. There must be a way for the simulation results to be compared to other published results. There is still a lot of work that has to be done to completely test the ideas created using real-world networks so that this thesis may be thoroughly analysed.